ӨЗБЕКСТАН РЕСПУБЛИКАСЫНДАҒЫ ҮЗЛИКСИЗ КӨРКЕМЛИК ТӘРБИЯ СИСТЕМАСЫНДА ЖЕКЕ АДАМНЫҢ ӨЗИНИҢ ДӨРЕТИЎШИЛИК МҮМКИНШИЛИКЛЕРИН ЖҮЗЕГЕ ШЫҒАРЫЎЫ мәселелери - Уразимова, Т.В. (SCIENCE and SOCIETY, 2018)
The article is devoted to the modern content and the role of the educational process. As attention increased in modern society to the problem of the continuous artistic education, not the last role plays here aesthetic education, contributing to enhance the development of world view, intellectual and creative potential of the individual. Therefore, the process of education should be based on creating conditions for education of creative personality, ready for dialogue, collaboration and co-creation in various spheres of life.
Keywords: педагогика; ижтимоий жараён; ўкитиш жараёни; методология; ўкитиш усуллари; инновацион технология; ижодкорлик